Pengaruh Metode Outdoor Studi Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPAS Kelas IV SD Negeri Gondrong 2 Kota Tangerang - Amanah, Eliyah; Zuliani, Rizki; Zamroni, Moh. (Peneliti.net, 2024)
This study discusses the effect of the Outdoor Study learning method on student learning outcomes in grade IV science science subjects. This study aims to determine whether there is an influence of the Outdoor Study learning method on student learning outcomes in class IV Science Science subjects. This research was conducted at SDN GONDRONG 2. The research method used was a quasi-experimental design with a non-equivalent control group design. Sampling was 60 students with class IV A 30 students as the control class and class IV B totaling 30 students as the experimental class. Power collection uses an instrument in the form of a description test that has been tested for validity and reliability. Based on the results of posttest calculations using the t-test at a significant level ???? = 0.05% obtained t-count (3.68) > t-table (2.0017) it can be concluded that the outdoor study method has an effect on student learning outcomes in science subjects material for class IV plant parts at SDN Gondrong 2.